Measures to prevent the bankruptcy of the debtor - Aviation Enterprise and extrajudicial procedures - Kozyreva, Valentyna P.; Gavrylishyn, Anatoliy P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The results of the market reforms, which took part in Ukraine, have confirmed the necessity of the further changes, especially in the system of the bankruptcy, which is considered below. Herewith, one of the least regulated practical issues is the process of application of the measures to avoid bankruptcy of the aviation companies.